2013
DOI: 10.2166/wst.2013.639
|View full text |Cite
|
Sign up to set email alerts
|

Sewage pre-concentration for maximum recovery and reuse at decentralized level

Abstract: Pre-concentration of municipal wastewater by chemically enhanced primary treatment (CEPT) was studied under controlled laboratory conditions. Both iron and aluminium-based coagulants were examined at gradually increasing concentrations (0.23, 0.35, 0.70 and 1.05 mmol/L). The CEPT sludge generated from different coagulation experiments was digested in batch anaerobic reactors, while the supernatant was tested in a dead-end microfiltration setup. The results of the study show that biogas yield was dramatically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…The concentration of dissolved pollutants and suspended sediment at every node in the sewer network is calculated for every time step using the InfoWorks ® Network Model. The governing equation at a node is given by conservation of mass, Equation (1). Pollutant inflows arrive from incoming conduits and any external sources, in this case, wastewater events (household discharges).…”
Section: Stochastic Sewer Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of dissolved pollutants and suspended sediment at every node in the sewer network is calculated for every time step using the InfoWorks ® Network Model. The governing equation at a node is given by conservation of mass, Equation (1). Pollutant inflows arrive from incoming conduits and any external sources, in this case, wastewater events (household discharges).…”
Section: Stochastic Sewer Modelmentioning
confidence: 99%
“…Resource recovery from wastewater is more effective at high concentrations. This can be achieved through dewatering processes at treatment plants [1][2][3] but another option is to limit wastewater dilution in the collection process [4]. Limiting wastewater dilution can be achieved by reducing domestic drinking water use, separation of storm/wastewater systems and preventing groundwater inflow by repairing/replacing broken pipes.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggested that the operating and maintenance costs of CEPT were higher than those of conventional primary treatment (Chagnon & Harleman, 2002), e.g. the operating costs of CEPT increased by about €0.06-0.10/m 3 wastewater treated, equivalent to €0.24-0.40/kg COD due to the use of chemicals (Diamantis et al, 2013). Moreover, the higher dosage of chemicals, especially at concentrations higher than 100 mg/L for iron or alum, might compromise the biogas productivity in the subsequent AD process.…”
Section: Technologies For Energy Recovery From Biosolidsmentioning
confidence: 99%
“…It has also been reported, in a WWTP in Mexico, that an annual operational cost of US$ 4 million was incurred due to CEPT with a mean treatment capacity of 4.49 × 10 5 m 3 /day, equivalent to US$ 0.024/m 3 wastewater (Harleman et al, 2002). In addition, the cost associated with CEPT was estimated to be about 0.1 €/m 3 in a wastewater treatment facility with a capacity of 500 m 3 /d where both alum and polymer were used (Diamantis et al, 2013). However, it should be noted that an increased amount of sludge is generated during CEPT, e.g.…”
Section: Cost-benefit Analysismentioning
confidence: 99%